2018
DOI: 10.1038/s41388-018-0521-8
|View full text |Cite
|
Sign up to set email alerts
|

mTOR kinase leads to PTEN-loss-induced cellular senescence by phosphorylating p53

Abstract: Loss of PTEN, the major negative regulator of the PI3K/AKT pathway induces a cellular senescence as a failsafe mechanism to defend against tumorigenesis, which is called PTEN-loss-induced cellular senescence (PICS). Although many studies have indicated that the mTOR pathway plays a critical role in cellular senescence, the exact functions of mTORC1 and mTORC2 in PICS are not well understood. In this study, we show that mTOR acts as a critical relay molecule downstream of PI3K/AKT and upstream of p53 in PICS. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 38 publications
1
85
0
Order By: Relevance
“…Network analysis of the downregulated proteins predicted P53 gene ( Tp53 ) as a key central hub molecule, networking directly with Aldh4a1, Aifm2, Cdc42ep3, Gstm5, Myocd , and so forth, and indirectly with Aqp2, Itga2b, Ifng , and Il4 (Figure 2F). As previously mentioned, PICS should involve P53‐P21Cip1 signaling to restrain prostate intraepithelial neoplasia (PIN) progression 18 in the absence of DNA damage and repair responses 24 . Indeed, several moderately upregulated genes included P53 direct effectors (genes: Foxa1, Casp1, Egfr, Casp6, Cx3cl1, Jun , and Pml ) and cellular senescence (genes: Lmnb1, Ets2, Hist1h2aa, Hist1h2ag, Hist1h2ah, Hist1h2aj, Hist1h2am, Hist1h2ap, Jun , and Rps6ka1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Network analysis of the downregulated proteins predicted P53 gene ( Tp53 ) as a key central hub molecule, networking directly with Aldh4a1, Aifm2, Cdc42ep3, Gstm5, Myocd , and so forth, and indirectly with Aqp2, Itga2b, Ifng , and Il4 (Figure 2F). As previously mentioned, PICS should involve P53‐P21Cip1 signaling to restrain prostate intraepithelial neoplasia (PIN) progression 18 in the absence of DNA damage and repair responses 24 . Indeed, several moderately upregulated genes included P53 direct effectors (genes: Foxa1, Casp1, Egfr, Casp6, Cx3cl1, Jun , and Pml ) and cellular senescence (genes: Lmnb1, Ets2, Hist1h2aa, Hist1h2ag, Hist1h2ah, Hist1h2aj, Hist1h2am, Hist1h2ap, Jun , and Rps6ka1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The progression of PIN lesions in the Pten‐KO model has been known to be constrained by PICS 18 . Pten loss has been shown to trigger PICS through a P53‐dependent pathway in mouse prostate tumorigenesis 18 and other cell models, 2,24 through mTORC1 and mTORC2 driven P53 protein stabilization. Since palpable tumors were collected and analyzed in our work, PICS might have been attenuated to allow the tumors to achieve the physical sizes, making predicting PICS from the omics data a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of alveolar epithelial cells from idiopathic pulmonary fibrosis patients also linked the activation of nuclear factor‐κB with reduced PTEN levels and both were associated with senescence, which is likely an initiating insult in lung fibrosis . Furthermore, mTOR kinase signaling is activated downstream of PI3K/Akt in PTEN‐depleted MCF7 cells . mTOR signaling has also been associated with the onset of p53‐induced cellular senescence in PTEN‐deficient mouse embryonic fibroblasts .…”
Section: Discussionmentioning
confidence: 99%
“…PTEN (phosphatase and tensin homolog) is a phosphatidylinositol‐3,4,5‐trisphosphate 3‐phosphatase, which is a main negative regulator of PI3K/AKT signaling . Dysfunction of PTEN mediates a variety of diseases, including tumorigenesis, diabetes mellitus, cardiovascular diseases, and so forth . Recently, it has been reported that PTEN expression is controlled by noncoding RNAs (ncRNAs) epigenetically or posttranslational modifications as well, such as ubiquitination, SUMOylation, or acetylation .…”
Section: Introductionmentioning
confidence: 99%
“…8 Dysfunction of PTEN mediates a variety of diseases, including tumorigenesis, diabetes mellitus, cardiovascular diseases, and so forth. 9 Recently, it has been reported that PTEN expression is controlled by noncoding RNAs (ncRNAs) epigenetically or posttranslational modifications as well, such as ubiquitination, SUMOylation, or acetylation. 10 Therefore, PTEN can be a biomarker for Wen-Ming Shen and Jin-Nan Yin contributed equally to this study.…”
Section: Introductionmentioning
confidence: 99%